Effect of major disasters on geographical mobility intentions: The case of the Fukushima nuclear accident - Eiji Yamamura; Yoshiro Tsutsui; Chisako Yamane; Shoko Yamane (Osaka University, Institute of Social and Economic Research (ISER), 2014)
This paper uses panel data from Japan to explore how the Great East Japan Earthquake influenced the intention to leave one's place of residence by comparing the same individuals' responses before and after the earthquake. Controlling for unobserved individual fixed effects and various individual characteristics, we found that (1) people were more willing to leave their place of residence after the disaster when they lived nearer to Fukushima, (2) the effect of the disaster on intention to leave was reinforced when respondents had a small child, and (3) after dividing sample by gender, such tendencies were observed among women but not among men. From the last finding, we conclude that differences between men and women in perceived risk lead to differences in mobility intentions.
Keywords: Q54; J15; J61; D89; 330; geographical mobility; disaster; perceived risk